EVALUASI KINERJA STASIUN TARIK DAN TARIF KA JENGGALA DENGAN METODE ATP DAN WTP - Abdillah, Hilmy Abid; Wicaksono, Achmad; Bowoputro, Hendi (Jurnal Mahasiswa Jurusan Teknik Sipil, 2020)
Tarik Station is a Class II Station located in Tarik, Sidoarjo. The problem that occurs at the Tarik station is that there are still many passengers who stand to wait for the arrival of the train because of the limited seating in the waiting room which is only available 24 seats and the long queue of ticket reservations at the station counter along 9 people queuing during peak hour. On 12 November 2014, PT. KAI (Persero) operated the Jenggala Train on the Mojokerto - Sidoarjo route to meet the mobility needs in the area. The purpose of this study was to determine the level of service of the Tarik Station according to the costumers, service improvement at the Tarik Station, improvement sketch of Tarik Station and the level of ability and willingness of Jenggala Train users to pay for train tickets. The analysis used for customer satisfaction in Tarik Station using Importance Performance Analysis (IPA) method, for service improvement Tarik Station, refer to the Minister of Transportation regulation No. 63 of 2019 concerning Minimum Service Standards People with Railway Transport and for ability and willingness to pay for Jenggala Train fare using Ability To Pay (ATP) and Willingness To Pay (WTP) methods. The results of the analysis of the Tarik Station have not met the desires of costumers and need improvement in terms of facilities like CCTV, security officers, ticket counters, waiting rooms and toilets. Facility improvements made were the addition of 2 CCTVs, 5 security officers, 2 ticket counters, 70 of waiting area and 6 toilets. The value of the ability to pay passengers of the Jenggala train is 116 Rp/km and the willingness to pay the passengers of the Jenggala train is 147 Rp/km and the fare of Jenggala Train is 130 Rp/km. Keywords: Railway, Jenggala, Operational Performance, Cross Capacity, IPA